2015
DOI: 10.18488/journal.aefr/2015.5.3/102.3.391.406
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Corporate Governance in Chinese Companies on Discretionary Accruals and Real Earnings Management

Abstract: This study investigates the influence of ownership structure and board characteristics on discretionary accruals and real earnings management using the data of A-shares in Chinese

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
24
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 35 publications
(32 reference statements)
5
24
1
3
Order By: Relevance
“…There is, however, evidence of a negative association between managerial ownership and the magnitude of earnings management [44,48,61,62]-for accrual-based earnings management. Hsu and Wen [34] documented that the association between the share of insider shareholdings and the level of real earnings management is significantly negative, which means that insiders with a significant share of ownership can effectively supervise managers conducting real earnings management.…”
Section: Managerial Ownership and Earnings Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…There is, however, evidence of a negative association between managerial ownership and the magnitude of earnings management [44,48,61,62]-for accrual-based earnings management. Hsu and Wen [34] documented that the association between the share of insider shareholdings and the level of real earnings management is significantly negative, which means that insiders with a significant share of ownership can effectively supervise managers conducting real earnings management.…”
Section: Managerial Ownership and Earnings Managementmentioning
confidence: 99%
“…Research on the relationship between the magnitude of real earnings management and the ownership structure of companies has been much more limited and has not necessarily focused on ownership concentration and managerial ownership, including that of [26][27][28][29][30][31][32][33]. Hsu and Wen [34] analyzed only the linear correlation between the percentage of insider shareholdings and the magnitude of real earnings management. The main motivator of this research was to check the significance of the ownership structure of the company in real earnings management as a factor relatively poorly reported in the current literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is targeted at fulfilling responsibilities for the board in the preparation of financial reports. In doing so, it increases the expectation that corporate governance may deter or minimise both manipulation of accrual based and manipulation of real activities (Hsu and Wen, 2015). Setting a corporate board structure could lead to many benefits at different levels of management and indeed helps the organisation to maximise earnings; minimise investment risk and enhance the firm's value (Abubakar, 2013;Liu and Tsai, 2015;Zgarni, Halioui, and Zehri, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Hsu and Wen (2015) investigated the impact of ownership structure and board characteristics on discretionary accruals and real earnings management. The results demonstrated that establishments with high shareholding proportion or extraordinary shareholding focus give managers incentives to control discretionary accruals for short-term profitability.…”
mentioning
confidence: 99%